A geroscience motivated approach to treat Alzheimer's disease: Senolytics move to clinical trials. (December 2021) - Gonzales, Mitzi M.; Krishnamurthy, Sudarshan; Garbarino, Valentina; Daeihagh, Ali S.; Gillispie, Gregory J.; Deep, Gagan; Craft, Suzanne; Orr, Miranda E.
Highlights: A poor understanding of mechanisms driving Alzheimer's disease pathogenesis presents obstacles for drug development. Cellular senescence is a promising target for therapeutic intervention in Alzheimer's disease. Clearing senescent cells improves brain structure and function in mouse models of Alzheimer's disease neuropathology. Senescent cells accumulate in the human brain with natural aging and Alzheimer's disease. Key considerations and strategies for targeting senescent cells in Alzheimer's disease clinical trials are discussed. Abstract: The pathogenic processes driving Alzheimer's disease (AD) are complex. An incomplete understanding of underlying disease mechanisms has presented insurmountable obstacles for developing effective disease-modifying therapies. Advanced chronological age is the greatest risk factor for developing AD. Intervening on biological aging may alter disease progression and represents a novel, complementary approach to current strategies. Toward this end, cellular senescence has emerged as a promising target. This complex stress response harbors damaged cells in a cell cycle arrested, apoptosis-resistant cell state. Senescent cells accumulate with age where they notoriously secrete molecules that contribute to chronic tissue dysfunction and disease. Thus, benefits of cell survival in a senescent fate are countered by their toxic secretome. The removal of senescent cells improves brain structure and function in rodent models at risk of developing AD, and in those with advanced Aβ and tau pathology. The present review describes the path to translating this promising treatment strategy to AD clinical trials. We review evidence for senescent cell accumulation in the human brain, considerations and strategies for senescence-targeting trials specific to AD, approaches to detect senescent brain cells in biofluids, and summarize the goals of the first senolytic trials for the treatment of AD (NCT04063124 and NCT04685590). This article is part of the Special Issue - Senolytics - Edited by Joao Passos and Diana Jurk.